Pengaruh Financial Distress, Umur Perusahaan, dan Konservatisme Akuntansi Terhadap Tax Avoidance - Idkhiyah, Nurul; Trisnaningsih, Sri; Widodo, Condro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Tax avoidance has become a critical issue in the taxation system, as it can reduce the government’s potential tax revenue. Companies often exploit weaknesses or loopholes in tax regulations as a strategy to minimize their tax expense. The purpose of this study is to assess and investigate the effect of financial distress, firm age, and accounting conservatism on tax avoidance. The study focuses on a population of property and real estate businesses listed on the Indonesia Stock Exchange between 2019 and 2023. This study employed a quantitative approach, including multiple linear regression analysis. The sample was drawn using a purposive sampling strategy, resulted in 13 firms and 65 observational data points. The results of the t-test (partial test) indicate that the financial distress variable has a significance value of 0,007 < 0,05 implying that financial distress has a significant effect on tax avoidance. The firm age variable show a significance value of 0,000 < 0,05, indicating that firm age also significantly affects tax avoidance. Meanwhile, the accounting conservatism variable yields a significance value of 0,182 > 0,05, suggesting that accounting conservatism has no significant effect on tax avoidance. Furthermore, the results of the F-test (simultaneous test) show a significance value of 0,000 < 0,05, indicating that financial distress, firm age, and accounting conservatism have a significant effect on tax avoidance. The findings of this study contribute theoretically by expanding the existing literature on tax avoidance determinants and offer practical implications that can support policymakers in evaluating and refining tax regulations.